PELLBA 4, Pertemuan Linguistik Lembaga Bahasa Atma Jaya Keempat : linguistik neurologi - Dardjowidjojo, Soenjono, 1938- (Penerbit Kanisius, 1991)
Neurolinguistics and language ability with reference to Indonesia; proceedings of seminar.